Does Social Science Inform Foreign Policy? Evidence from a Survey of US National Security, Trade, and Development Officials. - Avey, Paul C; Desch, Michael C; Parajon, Eric; Peterson, Susan; Powers, Ryan; Tierney, Michael J (International Studies Quarterly, 2022)
Scholars continue to debate the relationship of academic international relations to policy. One of the most straightforward ways to discern whether policymakers find IR scholarship relevant to their work is to ask them. We analyzed an elite survey of US policy practitioners to better understand the conditions under which practitioners use academic knowledge in their work. We surveyed officials across three different policy areas: international development, national security, and trade. We also employed multiple survey experiments in an effort to causally identify the impact of academic consensus on the views of policy officials and to estimate the relative utility of different kinds of research outputs. We found that policymakers frequently engage with academic ideas, find an array of research outputs and approaches useful, and that scholarly findings can shift their views. Key obstacles to using academic knowledge include practitioners' lack of time as well as academic work being too abstract and not timely, but not that it is overly quantitative. Additionally, we documented important differences between national security officials and their counterparts who work in the areas of development and trade. We suggest that this variation is rooted in the nature of the different policy areas.